Rejecting the “Therapy vs. Enhancement Distinction”: An Ethical Evaluation of Preimplantation Genetic Diagnosis Through Genetic Justice - Calderini, Guido (Université d'Ottawa / University of Ottawa, 2022)
The following work presents the ongoing philosophical debate regarding the use of biotechnology to improve human capabilities and attempts to apply the insights drawn from these debates to the regulation of non-medical uses of reproductive technology. After presenting the criticisms towards a hardline approach that would ban all attempts to enhance humans, we evaluate various alternative frameworks and adopt a framework called Genetic Justice, which can be understood as an application of Rawlsian distributive justice to biological assets. After improving on this moral framework by incorporating various institutional considerations into it, we apply it to the evaluation of non-medical uses of a screening technique called preimplantation genetic diagnosis and propose recommendations for its regulation.
Keywords: PGD; Genetic Engineering; Enhancement; Eugenics; Bioethics; Abortion